Coupling coordination of the provision of medical services and high-quality economic development in the Yangtze River Economic Belt - Yang, Shipeng; Yan, Hongtao; Gong, Yefang; Zeng, Siying (Frontiers in Public Health, 2024)
Background Promoting high-level coupling coordination between the provision of medical services (PMS) and high-quality economic development (HED) has emerged as a critical issue in China’s pursuit of high-quality development and is now a significant subject of concern in the area of welfare economics. Materials and methods Based on panel data from 11 provinces and municipalities in the Yangtze River Economic Belt, covering the period from 2010 to 2020, this study conducted an empirical analysis of the coupling coordination between PMS and HED and its influencing factors. Methods combined a comprehensive evaluation model, a coupling coordination model, and a panel Tobit model. Results The study found that: (1) Regarding the overall situation in the Yangtze River Economic Belt, the overall PMS demonstrates a fluctuating upward trend, while HED fluctuates within the lower range of 0.3 to 0.4. The coupling coordination degree between PMS and HED fluctuates within the moderate range of 0.5 to 0.6. (2) In terms of the spatiotemporal evolution trends, there still exists substantial spatial disparity among provinces and municipalities within the Yangtze River Economic Belt regarding PMS; nonetheless, this gap is gradually narrowing. Significant regional disparities are also observed in HED, with Shanghai, Jiangsu, and Zhejiang leading among the provinces and municipalities in the Yangtze River Economic Belt. The coupling coordination degree between PMS and HED displays notable spatial discrepancies, where downstream areas of the Yangtze River Economic Belt such as Shanghai, Jiangsu, and Zhejiang exhibit a higher coupling coordination degree compared to other provinces and municipalities. However, most provinces and municipalities outside this group remain at a moderately coordinated stage concerning the degree of coupling coordination between PMS and HED. (3) Economic development level and local government competition had a significant negative impact on coupling coordination between PMS and HED, whereas there was a significantly positive impact on the degree of fiscal autonomy and urbanization. Discussion This study contributes to comprehensively understanding the coupling and coordination relationship between the PMS and HED across provinces and municipalities in the Yangtze River Economic Belt. It provides empirical evidence for the collaborative evolution of PMS and HED.